Erfaringer med institusjonell etnografi - Magnussen, May-Linda (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Originally developed by the Canadian sociologist Dorothy E. Smith, institutional ethnography is an approach to research that aims to explore and challenge power relations in society. In Norway and the other Nordic countries, the approach is used by researchers in a variety disciplines and professional fields. In Experiences with Institutional Ethnography, we gain insight into several different researchers' motivation for, experiences with and reflections on delving into and using institutional ethnography in their own research. We gain insight into specific research processes and their attendant methodological approaches, into experiences of using key concepts from institutional ethnography, and into reflections on the researcher's role. This book will be a useful tool for researchers, master's students and research fellows who utilize - or are considering utilizing - institutional ethnography in their work.